Managerial Performance of Middle-Level Managers in Agricultural Schools in Northwestern Mindanao Philippines - Teonita Y. Velasco (CV. Literasi Indonesia, 2020)
This study examines the managerial performance of middle-level managers in Region IX and X covering state colleges and universities that offers agricultural courses. In analyzing the gathered data, percentage, weighted mean, t-test, and chi-square test were utilized. Findings of this research revealed middle-level managers were found very good in their leadership performance, in helping people to function as human beings, providing opportunities for each faculty/staff to grow, seeking to increase college effectiveness, and providing exciting and challenging work. Not enough evidence was established in the relationship between the organizational development values of middle-level managers in terms of helping people to function as human beings and providing opportunities for the faculty and staff to grow and the instructors’ teaching performance.